Waste treatment and Sustainable Bioelectricity Generation using Microbial fuel cell (JSSE - Journal of Science & Sustainable Engineering, 2023)
In the last decade, great attentions have been paid to microbial fuel cells (MFC) due to the possibility to be the solution for the three bigger world project – energy security, climate changes and waste management. Different from all the conventional wastewater treatment which are energy intensive, MFC can use waste as substrate/fuel to directly generate electricity through microbial reactions in anode and microbial/enzymatic/abiotic electrochemical reactions in cathode. In this sense, the MFC is an emerging technology for treat waste and produce wealth products (energy and some added value substance – organic acids, nutrients). Although, there are a large number of research in new materials and operational conditional to improve the MFC performance, as yet there are practical barriers, such as low power generation, expensive electrode materials and the inability to scale up MFC. Therefore, this work summarizes information about the recent advances in MFC research, focused on MFC configurations, material electrodes, and performances. Limitations and challenges in applying MFC to treat waste are also discussed, moreover future perspective pointed the new hot topics to solve these problems.